Electrophoretical studies of proteins of the hypopharyngeal glands and of the larval food of Melipona quadrifasciata anthidioides Lep (Hymenoptera, Meliponinae) - deMoraes, RLMS; BrochettoBraga, M. R.; Azevedo, A. (Springer, 1996)
The electrophoretical protein patterns of hypopharyngeal glands, larval food of Melipona, and royal jelly of Apis were compared.Since protein patterns of hypopharyngeal glands from newly emerged workers, brood cell provisioners and foragers are similar to freshly deposited larval food, the identical protein bands probably represent actual gland secretion. This suggests that, as in Apis, the glands secrete proteins to the larval food, and maintain this ability throughout life, although at slightly different intensities, according to the activity of the bees.The similarity on the electrophoretic profiles of the major larval food protein in Apis and Melipona is an interesting finding because of its probable evolutionary significance.
Keywords: hypopharyngeal gland; stingless bees; larval food; gel electrophoresis